Predictive value of TLR7 polymorphism for cetuximab‐based chemotherapy in patients with metastatic colorectal cancer. Issue 6 (21st June 2017) - Okazaki, Satoshi; Stintzing, Sebastian; Sunakawa, Yu; Cao, Shu; Zhang, Wu; Yang, Dongyun; Ning, Yan; Matsusaka, Satoshi; Berger, Martin D.; Miyamoto, Yuji; Suenaga, Mitsukuni; Schirripa, Marta; et al.
Abstract : The TLR7 and TLR9 signalings are implicated in the regulation of the immune system through type‐I interferon induction. Preclinical studies have demonstrated the immunomodulatory and antitumor effects of TLR7 and TLR9 agonists in combination with cetuximab. We tested the hypothesis that genetic variations in TLR7 and TLR9 and their downstream molecules IRF5 and IRF7 were associated with outcomes in metastatic colorectal cancer (mCRC) patients receiving cetuximab‐based chemotherapy. Six single nucleotide polymorphisms (SNPs) in TLR7, TLR9, IRF5 and IRF7 were tested for the association with RR, PFS, and OS in KRAS ‐wild type mCRC patients. Patients treated with FOLFIRI + cetuximab or FOLFIRI + bevacizumab in the FIRE‐3 trial served as a discovery set ( FIRE3‐Cet, n = 244) or a control set ( FIRE3‐Bev, n = 246), respectively. Patients treated with FOLFOX or SOX + cetuximab in the JACCRO‐CC05/06 trial served as a validation set ( JACCRO, n = 76). Genomic DNA isolated from tumor tissue samples was analyzed by PCR‐based direct sequencing. In the discovery cohort, patients with the TLR7 rs3853839 G/G variant showed a trend toward longer PFS than those with any C variants (median 10.0 vs . 11.8 months, HR 1.39, p = 0.092). This preliminary association was confirmed in the validation cohort, and those with the G/G genotype showed a PFS benefit compared with others (univariate: 9.1 vs . 11.6 months, HR 2.04, p = 0.005, multivariate: HR 2.02, 95% CI: 1.14–3.55, p = 0.015). This association was not observed in the control cohort. Our findings suggest that TLR7 rs3853839 predicts the outcome of cetuximab‐based chemotherapy in mCRC patients. Abstract : What's new? For patients with colorectal cancer, a particular genetic variant of TLR7 could mean the difference between life and death. Preclinical data have shown that TLR7 enhances the tumor‐killing ability of cetuximab; these authors tested six genetic variants of TLR7 and downstream molecules to find which ones affected survival of metastatic colorectal cancer. They found that patients who carried a G/G variant at one locus survived longer when treated with cetuximab than patients with any C variant. This marker could be useful in predicting which patients would benefit most from cetuximab.